Security analysis of data transmission in an IoT based platform for telemedicine - Olanrewaju, Rashidah Funke; Amuda, Idowu Rahaman; Hassan Abdalla Hashim, Aisha (IJPublication, 2021)
The Internet of Things offers an effective and increased job satisfaction when used for better services on the Internet. Decreased charges for materials and facilities on the network and breakthrough technology for modern society. Cryptography plays a major role in the defense of knowledge that has gained popularity as a result of digitization. The sharing of confidential personal data such as medical data continues to take place regularly across the globe; it is therefore crucial to protect data from unauthorized access by adversaries. One of the algorithms that is commonly used due to its exemplary security and use in extensive applications is the advanced encryption standard (AES) algorithm. This study proposes a modified folded pipeline architecture for resource restriction applications with an AES algorithm. Through time-multiplexing operations to a single functional unit, the folding transformation manages the circuit functions and decreases the time use for encryption and decryption by 30 percent and 20 percent, respectively. Using less power, the proposed architecture is implemented based on python programming language, thereby improving time and power requirements compared to the traditional algorithm. The work discussed in this thesis is important to the encryption and encryption of personalized electrocardiograph (ECG) signals for safe transmission are decrypted. This thesis work improved the throughput by 92.39% and 93.73% for encryption and decryption respectively and power by 96.93%, allowing its hardware to be implemented more efficiently than the traditional AES.